2008
DOI: 10.2967/jnumed.107.048249
|View full text |Cite
|
Sign up to set email alerts
|

Staging Pathways in Recurrent Colorectal Carcinoma: Is Contrast-Enhanced 18F-FDG PET/CT the Diagnostic Tool of Choice?

Abstract: 18 F-FDG PET/CT has gained wide acceptance for evaluation of recurrent colorectal carcinoma. However in clinical practice, contrast-enhanced CT (ceCT) is still the first-line restaging tool. The aim of this study was to investigate the value of contrastenhanced PET/CT (cePET/CT) as a first-line restaging tool with a special focus on the importance of the use of intravenous contrast. Methods: Fifty-four patients (17 women, 37 men; mean age, 60.3 y), referred for restaging of colorectal carcinoma, were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 22 publications
3
35
4
1
Order By: Relevance
“…Authors suggested that CE PET/CT might be considered as the first-line diagnostic tool for restaging of patients with colorectal cancer. 9 We totally agree with the study conducted by Soyka JD et al that corroborates with an added benefit of CE PET/CT over non CE PET/CT seen in our study. In our study, CECT (Chest, Abdomen, and Pelvis) correctly identified overall (TNM) stage in 57.4% (31/54) of patients and PET/CT correctly identified overall (TNM) stage in 72.2% (39/54) of patients.…”
Section: Discussionsupporting
confidence: 81%
“…Authors suggested that CE PET/CT might be considered as the first-line diagnostic tool for restaging of patients with colorectal cancer. 9 We totally agree with the study conducted by Soyka JD et al that corroborates with an added benefit of CE PET/CT over non CE PET/CT seen in our study. In our study, CECT (Chest, Abdomen, and Pelvis) correctly identified overall (TNM) stage in 57.4% (31/54) of patients and PET/CT correctly identified overall (TNM) stage in 72.2% (39/54) of patients.…”
Section: Discussionsupporting
confidence: 81%
“…Four therapeutic impact studies reported the findings from retrospective case series; 49,90,92,93 in one report the design was unclear;…”
Section: Resultsmentioning
confidence: 99%
“…The search identified seven therapeutic impact studies 49,[89][90][91][92][93][94] that sought to assess the value of FDG PET/CT in management. A further study published online as a pre-publication report was identified by one of our review team clinicians, and permission to include the study was obtained from the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with nonenhanced PET/CT, PET/ceCT provided additional information in 39 of the 54 patients (72%); this information had therapeutic relevance in 23 patients. This large number was primarily due to correct segmental localization of liver metastases, which is crucial for surgical therapy planning [7].…”
Section: Contrast-enhanced Studies With Pet/ct Hybrid Camerasmentioning
confidence: 99%